The effect of the organic fertilizer “Veto plus” and the marine algae extract “Unco sea weed” on leaf area, average weight and fruit hardness of pear trees of the “Cocia” variety. (Latakia University Journal -Biological Sciences Series, 2024)
The research was carried out in the village of Sharifa affiliated with the city of al Haffa in lattakia Govemorate during the season 2022-2023 on the pear tree "cocia" aged 25 years , the test included nine treatments, each treatment included three replicates, each tree one replicate, each turee one replicate in which the organic fertilizer Vito plus was used in addion to the seaweed extract Anco sea weed as a mixture and independently, where the effect of ingridents was studied relating to the average of the weigh and hardness of the fruit and on the leaf surface.The results appeared that static analysis exceeded leaf spray treatment włuch gave agreat result exceeded the control relating to leaf area and the treatment (Vito plus 2 cm3ł + Anco sea weed 0.5cm3/l) the highest value 35.80 cm2 as an average to the two years study, while the lowest value in the control 24.43cm2. also, this treatment gave the highest value to the fruit weigh and hardness as an average to the two years (136.86g , 3.52 kg/cm2) and eceeds the control which gave the lowest value (79.62g, 2.58kg/cm2) also, all leaf spray treatment with the organic fertilizer and seaweed extract exceeded all treaments comparing to the control when they used as a mixture to the two examples.